Open-sourced modeling and simulating tools for decision-makers during an emerging pandemic or epidemic - Systematic evaluation of utility and usability: A scoping review update - Rebecca Sophia Lais; Julia Fitzner; Yeon-Kyeng Lee; Verena Struckmann (Elsevier, 2024)
Introduction: The COVID-19 pandemic had devastating effects on health systems globally. Emerging infectious diseases and pandemics will persist as a global health threat and preparedness for an evidence based response becomes challenging for decision makers. Epidemiological modeling can and has supported decision-making throughout pandemics. This study provides an update of the review "Publicly available software tools for decision-makers during an emergent epidemic-Systematic evaluation of utility and usability"1. Research question: What epidemiological modeling tools for decision-makers are open-sourced available for the usage in emerging epidemics or pandemics and how useful and user-friendly are these tools? Methods: A scoping review was conducted. We identified relevant studies through a search of peer-reviewed (Medline Ovid, Embase Ovid, PubMed, Cochrane) and gray literature databases, search engines such as Google, searches through stakeholder websites as well as expert consultations. Results: Of the 66 identified epidemiological modeling tools, 29 were included and qualitatively assessed using five-point-rating scales. The tools showed a good baseline of user-friendliness with variations in assessed components, features and utility. Room for improvement was found, specifically the capability to incorporate external data sources, detailed population descriptions, and geographic resolution. Discussion: Development efforts should prioritize clear communication of uncertainties and expert review processes. Trainings for specific tools should be considered. Conclusion: Tool usage can enhance decision-making when adapted to the user's needs and purpose. They should be consulted critically rather than followed blindly.